Anti-cyclic citrullinated peptide antibodies in patients with primary Sjögren's syndrome (2005)
Primary Sjögren’s syndrome (pSS) is an autoimmune late onset disease characterised mainly by sicca symptoms. Lymphocytic infiltrate of the minor salivary glands and the presence of autoantibodies are the hallmarks of disease.1 The spectrum of pSS extends from an organ-specific autoimmune disorder (autoimmune exocrinopathy) to a systemic process that may involve the musculoskeletal system, leading to arthralgias and arthritis. In the latter case differential diagnosis with other autoimmune diseases like rheumatoid arthritis (RA) is a challenge. In these situations, specific antibodies may be useful for making a correct diagnosis and, consequently, guide treatment. Anti-cyclic citrullinated peptide (anti-CCP) antibodies have been shown to be a specific marker for the diagnosis of RA.2 They bind to determinants rich in the unusual amino acid, citrulline, generated by deamination of arginine.3 We have read the recent article by Gottenberg et al,4 in which a 7.5% prevalence of anti-CCP antibodies in 134 French patients with pSS was reported. Here, we describe a similar experience in Colombian patients with pSS.